Pengaruh Ukuran Perusahaan, Return on Asset (ROA), Net Profit Margin (NPM), Leverage, Debt to Equity Ratio (DER), dan Kepemilikan Institusional terhadap Praktik Income Smoothing pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia pada Tahun - Purnamasari, Lisa; Wibisono, Haris; Immanuela, Intan (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2018)
This study aims to prove empirically that company size, return on assets (ROA), net profit margin (NPM), leverage, debt to equity ratio, and institutional ownership affect the income smoothing practice on manufacturing companies listed in the Indonesia Stock Exchange in 2011 through 2015. The research data is obtained from the company's financial report published on the website of Indonesia Stock Exchange. Sample in this research is 55 companies which according to sample criterion (purposive sampling). Hypothesis testing using logistic regression analysis with the help of SPSS program version 17. The results of this study are not able to prove that the variable size of the company, Return On Assets (ROA), Net Profit Margin (NPM), leverage, Debt to Equity Ratio, and institutional ownership affect the practice of income smoothing.